TINJAUAN HUKUM PIDANA TERHADAP PERTIMBANGAN PUTUSAN LEPAS HAKIM PADA TINDAK PIDANA KORUPSI TANAH KAS DESA KEMBANGSONO (STUDI PUTUSAN NOMOR 281 PK/PID.SUS/2021) - Djauhari, Risky Ridho (Recidive : Jurnal Hukum Pidana dan Penanggulangan Kejahatan, 2023)
This study aims to find out and examine the criminal law arrangements for corruption in Indonesia and examine through a review of criminal law regarding the basis for the judge's legal considerations in imposing a release decision on decision number 281 PK/Pid.sus/2021. The legal research method used by the author is a prescriptive normative legal research method. The approach used in writing this law is a case approach and a statutory approach. The collection technique used by the author is a literature study by reviewing and studying primary and secondary legal materials. Technical analysis of data using the deduction method. The results of this study indicate that regarding criminal law arrangements related to criminal acts of corruption regulated in Law Number 31 of 1999 jo. Law Number 20 of 2001. Apart from that, from the review decision that has been reviewed, the author is of the opinion that the acquittal decision handed down by the panel of judges at the Supreme Court was appropriate and accurate because the actions committed by the convict did not fulfill the elements required contained in the formulation of the articles.